Management and Prognosis of Head and Neck Cancer Patients during the COVID-19 Pandemic - Giuliano Lozer Bruneli; Priscila Marinho de Abreu; Jhully Oliveira Ferreira; Camila Batista Daniel; Jéssica Graça Sant'Anna; Roberta Ferreira Ventura Mendes; Brena Ramos Athaydes; Mariane Vedovatti Monfardini Sagrillo; José Roberto Vasconcelos de Podestá; Marco Homero de Sá Santos; Jeferson Lenzi; Evandro Duccini de Souza; et al. (Revista Brasileira de Cancerologia)
Introduction: The COVID-19 pandemic raised the necessity to implement measures for managing patients with head and neck squamous cell carcinoma (HNSCC). Objective: To evaluate the measures adopted by an oncological hub during the COVID-19 pandemic and investigate whether the SARS-CoV-2 infection and viral load changed the outcomes of head and neck cancer patients. Method: Patients were tested for SARS-CoV-2 using real-time quantitative reverse transcription polymerase chain reaction and rapid COVID-19 antigen testing before surgery between October 2020 and November 2021. Clinical outcomes were compared by the presence of SARS-CoV-2 infection, considering prognostic factors for HNSCC patients, such as preexisting comorbidities and tumor staging. Results: Of the 194 patients recruited, 99 cases confirmed diagnoses of HNSCC and underwent surgical treatment. The most frequent comorbidities were arterial hypertension and diabetes mellitus. The oral cavity and larynx were the most affected anatomical sites, 51% and 33%, respectively. A total of 61.6% of the cases were classified as T3/T4 and 53.4% did not have lymph node involvement. Presence of comorbidities and lymph node metastasis were associated with reduced survival. Of the 99 cases confirmed, 8.1% (8/99) were infected with SARS-CoV-2, but no differences in overall survival according to SARS-CoV-2 infection (p = 0.086) were noticed and the viral load was not associated with vital status (p = 0.456). Conclusion: The presence of SARS-CoV-2 infection did not influence overall survival in head and neck SCC patients. This is the first study to describe these findings in an oncological care center in the State of Espírito Santo, Brazil.